ANALISIS PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KNERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi di Sekolah Menengah Pertama Negeri kecamatan Ulujami kabupaten Pemalang Propinsi Jawa Tengah) - Sunarsi Benediktus, 11.52.02.0015 (Students Journal of Economic and Management, 2013)
The study is intend to test and analyze the influence of work discipline and work motivation toward teacher performance with mediation job satisfaction at goverment yunior high school in district of Ulujami, residence of Pemalang Central Java; Sampling technique are non probability quota sampling, purposive sampling with 131 goverment teachers, technique of data test are validity test, reliability test, double linier regresion test, partial hypothesis test with t test, simultan hypothesis test with F test, and mediation analysis with Sobel test. The result of mediation test with Sobel test are job satisfaction does not mediate work discipline toward teachers performance, but job satisfaction proves to mediate work motivation toward teachers performance; It means work discipline is more effective influencing directly toward teachers performance than by controlling job satisfaction and work motivation effective in direct or indirect influencing toward teachers performance at goverment yunior high school in district of Ulujami, residence of Pemalang Central Java. Keyword : Work Discipline, Work Motivation, Job Satisfaction and TeacherÂ Performance